Legal Counseling Implementation of Registration and Brand Permits for MSME Actors - Arief Budiono; Rina Arum Prastyanti; Nico Irawan; Nurjannah Septyanun; Kaka Ismail Saputro; Munadia Rosada (Indonesian Scientific Journal, 2022)
A brand is a sign or characteristic of a product. Giving a brand to goods and or services distinguishes the product from other products. With the brand as a differentiator between the products and other products, producers can easily introduce their goods and or services to consumers. For a brand to exist in the constituent system, trademark ownership must be registered. This is because, without registration, the brand owner cannot claim absolute ownership. In conducting counseling/service, we conducted a literature study on the Implementation of Registration and Brand Permits for MSME Actors. The writers also made preparations by providing facilities and infrastructure for these activities. We also determined the time of the activity implementation cooperatively with the implementing team, and determine and study the material to be delivered in legal counseling activities. The trademark registration process can also currently be carried out online at the website https://brand.dgip.go.id/. This website was available since the breakthrough of the Directorate General of Intellectual Property of the Ministry of Law and Human Rights.